Cross‐scale interactions among bark beetles, climate change, and wind disturbances: a landscape modeling approach. Issue 3 (1st August 2013) - Temperli, Christian; Bugmann, Harald; Elkin, Ché
Abstract : Bark beetles are a key forest disturbance agent worldwide, with their impact shaped by climate, forest susceptibility, and interactions with other disturbances such as windthrow and fire. There is ample evidence of the interactions among these factors at small spatial and temporal scales, but projecting their long‐term and landscape‐scale impacts remains a challenge. We developed a spatially explicit model of European spruce bark beetle ( Ips typographus ) dynamics that incorporates beetle phenology and forest susceptibility and integrated it in a climate‐sensitive landscape model (LandClim). We first corroborated model outputs at various spatial and temporal scales and then applied the model in three case studies (in the Black Forest, Germany, and Davos, Switzerland) that cover an extended climatic gradient. We used this model and case study framework to examine the mechanisms and feedbacks that are driving short‐term and long‐term interactions among beetle disturbance, climate change, and windthrow, and how they may shift in the future. At the current cold‐wet end of the Norway spruce ( Picea abies ) distribution, climate change is projected to increase temperature and drought, such that beetles become a more dominant disturbance agent. At the warm‐dry end of the spruce distribution, where, under current climate, beetle outbreaks are confined to the simultaneous occurrence of drought and windthrow, the simulated level of drought alone sufficed for triggering beetle outbreaks, such that elevated drought‐ and beetle‐induced spruce mortality would negatively feed back on beetle disturbance in the long term. This would lead to receding beetle populations due to the local extinction of Norway spruce. These results suggest that, depending on initial environmental conditions, climate change may shift the importance of direct and indirect drivers of disturbances. These shifts may affect the sign and strength of cross‐scale disturbance interactions and may impact the cost–benefit trade‐off between beetle suppression and preventive management strategies.